Paper ontologies: reading Sterne with Bruno Latour. Issue 2 (23rd February 2017) - Lupton, Christina
ABSTRACT: This article takes a critical approach to the possibility of applying Bruno Lator's work to Tristram Shandy. Sterne is both reflexive about the impossibility of representing the material work and determined to do just that in relation to his book. But these are competing tendencies in Latour's terms, difficult to judge in the context of a single work. Latour's recent language for Fiction as a "mode" ultimately leaves us without a way to distinguish between texts that are self-conscious and those that aren't.